Mechanical Properties of Solid Biomass as Affected by Moisture Content - Mateusz Przywara; Regina Przywara; Wojciech Zapała; Ireneusz Opaliński (AgriEngineering, 2023)
The objective of the study was to examine the influence of moisture content on the mechanical properties of solid biomass, which is important for storage and handling. Mechanical properties involving powder flowability were determined with a Jenike shear tester. The materials tested were powdered biomass: sunflower husks, apple pomace, dried distillers grains with solubles (DDGS), and meat and bone meal. In static operations in which powdered biomass is generally under a significant load, such as in silos, moisture deteriorates the mechanical properties of biomass and increases its cohesion. In the case of DDGS, an additional slight decrease in stress was observed for samples with the highest moisture content, which was above 20%. For meat and bone meal and sunflower husks, a lubrication phenomenon was clearly observed, in which biomass samples with increased moisture content manifested better flowability, requiring lower boundary shear stresses than less moist samples. For apple pomace samples, with normal stresses above 50 kPa, the addition of moisture above 10% did not change the values of the observed shear stresses, indicating the stability of their properties. The use of powdered biomass with higher moisture contents, at above 10%, should be avoided, as such material can lead to overhangs in tanks and silos.